153 COMPARATIVE NON-HIGH-DENSITY LIPOPROTEIN CHOLESTEROL LOWERING BETWEEN GEMFIBROZIL AND STATINS IN DIABETES MELLITUS. (1st January 2006) - Hsia, S. H.; Harris, M. M.; Lee, M. L.; Charles, R.
Abstract : Recent studies suggest that non-HDL cholesterol (NHDL) may be a better predictor of risk than LDL cholesterol (LDL). Gemfibrozil and statins lower NHDL through different effects on lipoproteins; NHDL may represent a unifying index of risk reduction. Purpose: We directly compared the NHDL-lowering efficacy of gemfibrozil versus different dose equivalents of statins in patients with diabetes mellitus. Methods: Retrospective analysis of patient data obtained from a diabetes referral clinic. Fasting lipid profiles before and after a 4- to 8-week treatment period of a fixed dose of lipid-lowering monotherapy were collected from lipid-lowering, agent-naïve adult diabetic subjects. Patients with evidence of concurrent medical illnesses, alcoholism, suspicion of dietary or medication noncompliance, use of other lipid-altering drugs, or weight change ≥ 10 lbs over the treatment interval were excluded. The primary outcome was the percent change in NHDL across groups receiving gemfibrozil 600 mg bid (G), pravastatin 10 mg (S1), pravastatin 20 mg/simvastatin 10 mg (S2), or pravastatin 40 mg/simvastatin 20 mg or higher dose equivalent (S3); secondary outcomes included changes in fasting triglycerides (TG), total (TC), HDL (HDL), and LDL cholesterol. Results were analyzed as unadjusted comparisons and after multivariate adjustment for age, gender, hemoglobin A1c changes, BMI, and the respective baseline lipid levels. Results: A total of 126 datasets were available for analysis. The Table shows percent changes from baseline, and statistical significance of the change relative to the corresponding effect of gemfibrozil based on the multivariate adjustment (*indicates p < .05). The NHDL-lowering effect of gemfibrozil was significantly greater than that of the S1 group but significantly less than that of the S2 or S3 group. Conclusions: In this retrospective study, we found that gemfibrozil reduced NHDL more than pravastatin 10 mg but less than pravastatin 20 mg/simvastatin 10 mg. This finding demonstrates the potential utility of using NHDL as a unifying lipid-lowering index to compare different classes of agents and is consistent with the modest (but significant) cardiovascular event reduction known to occur with gemfibrozil.